1955
DOI: 10.1037/h0044634
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual performance as related to emotional instability in children.

Abstract: See (10) for fuller description of basis for making judgments on the quality of each design.4 Samples of the original designs are given in the Cornell-Coxe manual (5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1963
1963
1964
1964

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A number of studies indicate that there is some relation between personality maladjustment and cognitive deficit. Granick (1955) demonstrated that children with relatively mild personality disturbances were inferior in visual motor performances to children with more healthy personalities although similar on the Stanford-Binet Intelligence Test. Psychotic children, when compared with normal children (Schulman, 1953), gave more inadequate responses on the Gelb-Goldstein-Weigl-Scheerer Object Sorting Test.…”
Section: University Of Massachusettsmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of studies indicate that there is some relation between personality maladjustment and cognitive deficit. Granick (1955) demonstrated that children with relatively mild personality disturbances were inferior in visual motor performances to children with more healthy personalities although similar on the Stanford-Binet Intelligence Test. Psychotic children, when compared with normal children (Schulman, 1953), gave more inadequate responses on the Gelb-Goldstein-Weigl-Scheerer Object Sorting Test.…”
Section: University Of Massachusettsmentioning
confidence: 97%
“…The California Test of Personality was selected because this test provides an objective measure of adjustment, is designed for children between the ages of about 10-15 years, and has adequate reported reliabilities in the .90s (California Test Bureau, 1949). In addition, this test has been previously used in selecting children of different personality adjustment levels (Granick, 1955;Taylor & Combs, 1952).…”
Section: Test Materialsmentioning
confidence: 99%
“…Yet Hewitt & Jenkins (1946) found an association between over-inhibited behaviour and low I.Q., and unsocialized behaviour and high I.Q. Different cognitive functions have rarely been considered, but in one study emotionally disturbed children did particularly poorly on visual-motor tests (Granick, 1955). Academic achievement is often low even when the level of intelligence is normal (Salzinger, 1957).…”
mentioning
confidence: 99%
“…The factors which have been related to differences between verbal and performance I.Q. 's include such diverse ones as language disability, educational limitations, mixed cerebral dominance, concrete or abstract approaches to tasks, temporary emotional upset, delinquency, neurotic trends, gross behavior disorder, and organic deterioration (3,9,34,55,84). This large array of variables is discouraging in that it provides no simple explanation for the discrepancy between verbal and performance scores in a particular case.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%